Phonological Aspects in the Arabic Dictionary: The Arabic Dictionary in your Hands as an Example Namûzajan/ Al-Jawậnibu as-Shautiyah fi al-Mu’jam al-Arabiy: Al-Mu’jam al-Arabiyu baina Yadaik - Muzadi, Narul Hasyim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractAs a system, language is both a systematic and a subsystem. One of the subsystems is phonology. Phonology is a field or level of study in linguistics that discusses everything related to the sounds of language. Phonetics as a branch of phonetics discusses the sounds of language that do not affect meaning, while phonology discusses the sounds of language that affect meaning. This research belongs to the category of qualitative research with a literary study approach. The data collection method used in this research is to collect textbooks, journals, scientific articles, and literature reviews that contain the concept under study. The primary data source for this research is the dictionary of Abdul Rahman bin Ibrahim Al-Fouzan, Mukhtar Al-Tahir Hussein, and Muhammad Abdul Khaliq Muhammad Fadl titled